Advances in Comparative Colonial Toponomastics - Levkovych, Nataliya (Koloniale und postkoloniale Linguistik ;, 2020)
For the better understanding of the cultural and linguistic impact of colonialism on the shaping of the world as we know it today it is necessary to take account of the Europeanization of the map of the extra-European countries.To achieve this goal Comparative Colonial Toponomastics (CoCoTop) investigates the place names which were coined in the era of colonialism in the erstwhile possessions of European colonizer nations. This edited volume offers new insights into the toponomastic manifestations of Danish, French, German, Italian, and Spanish colonialism. The focus is on hitherto unexplored macrotoponyms and microtoponyms. Their structural and functional aspects are described. They are linked to the colonial history of the various nations involved. A general toponomastic framework beyond CoCoTop is presented additionally. Several of the papers mark the starting point of recently initiated new research projects.The volume is of special interest to onomasticians, scholars working in colonial and postcolonial linguistics, and historians of colonialism.